Jewish Women Pioneers in the Civil Rights Movement Betty Friedan - MELADZE, Eka (Journal in Humanities, 2025)
The Civil Rights Movement was a turning point in American history, which sought to bring an end to racial segregation and discrimination (Shultz, 2023). Jewish women made significant contributions to the civil rights movement in the United States. This is how Debora Shultz, author of one of the articles about civil rights movements in the U.S., describes Jewish women’s contribution to this process” Jewish women put their lives on the line to fight racism and white supremacy in the Southern civil rights movement and contributed professional skills and organizational clout to move the civil rights agenda forward throughout the country”. Their involvement often intersected with their commitment to social justice and their understanding of the historical oppression faced by both African and Jewish communities (Shultz, 2023). Jewish women in the civil rights movement fought for equality, highlighting the interconnectedness of different struggles for justice and equality in America. Although individuals like Martin Luther King Jr. and Rosa Parks are frequently at the forefront of conversations about this era, Betty Friedan, a well-known Jewish feminist and novelist, should not be disregarded for her influence (Shultz, 2023). This article examines Betty Friedan’s numerous contributions to the civil rights movement and her societal effect, illuminating the ways in which her feminism interacted with and influenced the larger fight for civil rights. Betty, Friedan, a prominent Jewish feminist and author, was a key figure in this movement. Her 1963 book, “The Feminine Mystique,” challenged the idealized view of femininity as social domestic, sparking the second wave of feminism. Friedan co-founded the National Organization of Women (NOW) in 1966, advocating for equal rights, pay, and reproductive rights for women. Her legacy continues to influence feminist and social justice movements today. Keywords: Civil Rights, Feminism, Betty Friedan, Jewish women